Clinical Outcomes of Negative Pressure Wound Therapy in the Management of Complex Abdominal Wounds - Ahmed Abu-Gharsa, (AlQalam Journal of Medical and Applied Sciences, 2026)
Complex abdominal wounds, resulting from trauma, surgical complications, or infection, present significant clinical challenges, including prolonged healing, high complication rates, and substantial healthcare costs. Negative Pressure Wound Therapy (NPWT) has emerged as an advanced treatment modality, yet its comprehensive outcomes in abdominal wounds require systematic evaluation. This study was conducted to systematically review and analyze the clinical, practical, and economic outcomes of NPWT in the management of complex abdominal wounds, with particular focus on healing rates, complication reduction, hospital stay duration, and cost-effectiveness. A comprehensive literature search was conducted across PubMed, ScienceDirect, Wiley Online Library, and Cochrane databases for studies published between 2015-2025. Inclusion criteria encompassed randomized controlled trials, cohort studies, and systematic reviews evaluating NPWT in abdominal wound management. Data extraction and quality assessment were performed using PRISMA guidelines and Cochrane risk-of-bias tools. Analysis of 42 included studies (total n=5,217 patients) revealed that NPWT significantly accelerated wound healing (mean reduction in healing time: 35.2%, 95% CI 28.7-41.8%, p<0.001), reduced surgical site infections (relative risk 0.64, 95% CI 0.52-0.78), and shortened hospital stays by an average of 6.3 days (95% CI 4.8-7.9 days, p<0.001). Fistula formation occurred in 8.7% of NPWT cases compared to 11.3% with conventional therapy (p=0.08). Cost analysis demonstrated an initial higher expenditure but overall savings of 23.4% per patient due to reduced complications and shorter hospitalization. NPWT represents an effective, cost-saving intervention for complex abdominal wounds when applied according to standardized protocols. Future research should focus on optimizing patient selection criteria and developing region-specific cost-effectiveness models.